PENGGUNAAN BORAKS PADA SAMPEL BAKSO OLEH PEDAGANG BAKSO DI KECAMATAN KEBAYORAN BARU, JAKARTA SELATAN - Ony Linda; Erna Rachmawati; Sarah Handayani (ARKESMAS [Arsip Kesehatan Masyarakat], 2016)
The Use of Borax on Meatball Samples by Meatballs Traders in Kebayoran Baru Sub Distrik, South Jakarta Introduction. Borax is not an additional food category. Therefore, meatballs containing borax are notsafe for consumption. This study aims to determine borax content in meatballs by meatball traders whosell in the district of Kebayoran Baru, South Jakarta. The study also identified variables related to boraxuse.Methods. The type of this research is quantitative analysis with cross sectional approach. Samples takenin the form of meatballs and traders who make and sell their own meatballs permanently in the DistrictKebayoran Baru. Total samples are 56 people. Data collection was conducted from February to August2015. The results of the measurement of borax content were analyzed in a laboratory. Bivariate analysisuse Chi Square test.Results. The results showed that the positive traders used the borax of 28.6%, low education level(73.2%), knowledgeable (55.4%), long trading had more than 17 years (91.1%), had a positive attitudetoward Borax (62.5%), have good motivation (57.1%), have positive perception on regulation (58,9%),have easy to get borax (53,6%), have influence of weak friend including good (58, 9%). The result of chisquaretest showed that the variables that have statistical correlation with borax usage are education,knowledge, motivation, trader's perception on the regulation, ease of obtaining materials, and guidanceand supervision.Conclusion. This research concludes that knowledge and low education become one of the causes oftraders still use borax in their meatballs. It also was influenced by low coaching and supervision.